2023
DOI: 10.3390/ani13152460
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Nanoparticles as Potential Antioxidants to Improve Semen Quality in Boars

Pavel Horky,
Lenka Urbankova,
Iqra Bano
et al.

Abstract: Selenium is an essential compound which can influence the fertility of boars by a greater margin. In past decades, research was mainly focused on a bioavailability of various selenium forms and the effect on semen quality. Recently, nanotechnology has expanded the possibilities of selenium supplementation research. Twenty-one Duroc boars (three groups with seven boars each) were included in this experiment with the first group being a control group with no selenium supplementation, and the second group being s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Horkey et al reported that the oral supplementation of selenium nanoparticles has not shown an improving effect on sperm quality. However, this could be considered a safe alternative to inorganic selenium, as well as having the potential to enhance the antioxidant properties of the semen of boars ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Horkey et al reported that the oral supplementation of selenium nanoparticles has not shown an improving effect on sperm quality. However, this could be considered a safe alternative to inorganic selenium, as well as having the potential to enhance the antioxidant properties of the semen of boars ( 20 ).…”
Section: Introductionmentioning
confidence: 99%